Penerapan Metode Dempster Shafer Untuk Mendiagnosa Penyakit Pada Tanaman Pepaya - Novi Putriani Giawa; Preddy Marpaung (Jurnal Sistem Informasi dan Teknologi Jaringan (SISFOTEKJAR), 2021)
The papaya plant is one of the plantation crops that is very important because it is a source of vitamins, which help in strengthening the immune system which can help prevent infection. In cultivating these plants, several problems often occur, such as diseases in papaya plants where when they are attacked by disease and in the absence of treatment, farmers will experience losses, both crop yields, and plant quality will decrease. Based on this, a tool in the form of an expert system is needed in order to diagnose papaya plant diseases. The Dempster Shafer method is the method used in this study, which can process data by providing evidence-based on the density value. This study manages 5 types of diseases and 13. The results show that this research can be used as a tool in diagnosing papaya plant diseases so that it is expected to help farmers in handling diseases that attack papaya plants quickly and precisely and can increase profits from crop yields.